ANXIETY ON DEALING FINAL EXAMINATION AS DETERMINANT CHANGES OF THE MENSTRUAL CYCLE TO FEMALE STUDENTS OF SEHAT PPNI MOJOKERTO - Tria Wahyu Ningrum (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Women will experience menstrual cycle changes during her productive life. In its effect on the menstrual cycle, anxiety involves the neuroendocrinology system as a major system of its role in female reproduction. This research aimed to determine whether the anxiety as the determinant of menstrual cycle changes in students of Midwifery Department Bina Sehat PPNI Health science institute Mojokerto. This research used comparative analytic design with cross-sectional approach. Its population was all student of Midwifery Department level III Bina Sehat PPNI Health science institute Mojokerto which is a final exam 128 people. The number of samples was 28 respondents using simultaneous sampling technique for 15 days. The data were analyzed by using chi-square test. The result showed that 6 respondents had moderate anxiety, most of them had normal menstrual cycle, 12 students (75%) and 7 respondents had severe anxiety, most of them had oligomenorrhea that was 5 students (71, 4%), chi-square test results obtained Ï = 0.003, means Ï <Î± (0.05) so that H0 is rejected means there is anxiety becomes the determinant of menstrual cycle. It is suggested to female students to be able to improve their knowledge about the menstrual cycle and excessive anxiety control with technical technique and hopefully can give motivation and good coping to students